2021
DOI: 10.1371/journal.pone.0249625
|View full text |Cite
|
Sign up to set email alerts
|

Cost of pre-exposure prophylaxis delivery in family planning clinics to prevent HIV acquisition among adolescent girls and young women in Kisumu, Kenya

Abstract: Introduction Oral pre-exposure prophylaxis (PrEP) is increasingly being implemented in sub-Saharan Africa. Adolescent girls and young women (AGYW) in Kenya contribute more than half of all new infections among young people aged 15–24 years, highlighting the need for evidence on the cost of PrEP in real-world implementation to inform the budget impact, cost-effectiveness, and financial sustainability of PrEP programs. Methods We estimated the cost of delivering PrEP to AGYW enrolled in a PrEP implementation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
2
6
1
1
Order By: Relevance
“…However, we can compare the mean clinical-service unit costs of HTS, ART, and PrEP to those of previous studies conducted in Kenya and Malawi. Our direct clinical service unit costs of US$5 for HTS in Kenya is similar to previous estimates [ 40 , 41 ] though our unit costs of US$162 and US$127 for ART and PrEP are slightly lower than earlier studies [ 42 47 ]. Our direct clinical service unit costs of US$25 for HTS and US$260 for ART in Malawi are somewhat higher than those of previous studies [ 48 53 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, we can compare the mean clinical-service unit costs of HTS, ART, and PrEP to those of previous studies conducted in Kenya and Malawi. Our direct clinical service unit costs of US$5 for HTS in Kenya is similar to previous estimates [ 40 , 41 ] though our unit costs of US$162 and US$127 for ART and PrEP are slightly lower than earlier studies [ 42 47 ]. Our direct clinical service unit costs of US$25 for HTS and US$260 for ART in Malawi are somewhat higher than those of previous studies [ 48 53 ].…”
Section: Discussionsupporting
confidence: 86%
“…A study in Zimbabwe reported the cost per PrEP client initiated as $238 while another study in Kenya reported an overall cost of $256 [11,24]. Compared to our calculated costs per person-month, ranging from $37 to $61, other studies were also lower at $26.52 under study settings or $16.54 under MOH scenario and $21.32 and $28.92 study, $14.52 for adolescent girls and young women [12,25,26]. One possible reason for these differing results are the relatively low PrEP client volumes in these programs compared to those reported in other studies, which ranged from 219 to almost 5000.…”
Section: Plos Global Public Healthcontrasting
confidence: 66%
“…The costs of PrEP programs implemented in routine care settings in sub-Saharan Africa (SSA) are largely unreported and those that are, have thus far focused primarily on targeting key populations including female sex workers (FSW), men who have sex with men (MSM), and priority populations such as adolescent girls and young women (AGYW). Evidence demonstrating the variations in costs of these different PrEP programs, service delivery strategies, and resource utilization in SSA is limited, with only a few demonstration projects having published the costs of providing PrEP in these settings [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of PrEP can be affected by many issues, such as limited resources and overstretched health systems, especially in the Sub-Saharan context ( Bigna et al, 2016 ). PrEP is an effective HIV intervention tool to existing interventions ( Allende & Acuña, 2017 ); however, the issue of availability has always come in the way of ensuring its success ( Wanga et al, 2021 ). Availability of PrEP was mentioned in eleven (11) articles in different contexts as; a potential facilitator to the willingness to use PrEP ( Ahouada et al, 2020 ; Frankis et al, 2016 ) and as the factor that influences PrEP uptake ( Ahouada et al, 2020 ; Chakrapani et al, 2015 ; Dean et al, 2023 ; Diabaté et al, 2021 ; Galea et al, 2011 ; Kimani et al, 2022 ; Pelletier et al, 2019 ); refer to Table 3 Availability of PrEP does not always imply improved uptake and acceptability of PrEP, hence the need to ensure accessibility of the available PrEP to MSM.…”
Section: Resultsmentioning
confidence: 99%